The protection of the rare species Crambe tataria Sebeók (Brassicaceae) in the Bashkir Cis-Urals - Maslova Natalya; Elizaryeva Olga; Muldashev Albert (BIO Web of Conferences)
Crambe tataria Sebeòk (Brassicaceae Burnett) is a rare species of flora of the Cis-Urals and the Southern Urals (the territory of the Republic of Bashkortostan). This species is in a near threatened state. The species is included in The Red Data Book of the Republic of Bashkortostan (2021). Crambe tataria is a valuable economically useful wild plant, belongs to the group of the Wild Relatives of Cultivated Plants. On the territory of the republic, this is a poorly studied species, located near the eastern border of the areal, known in the Bashkir Cis-Urals and the western foothills of the Southern Urals. The study and protection of this species is carried out in natural habitats (in situ) and when cultivated in nursery conditions (ex situ). The destruction of natural habitats is the main threat to the existence of this species. A method for creating artificial coenopopulations of this species (ex situ) is being developed.